MICROBIAL SYMBIONTS IN MARINE SPONGES: Marine natural product factory - Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2008)
Marine sponges (phylum Porifera) are among the oldest multicellular animals (metazoans), the sea’smost prolific producers of bioactive metabolites, and of considerable ecological importance due to theirabundance and ability to filter enormous volumes of seawater. In addition to these important attributes,sponge microbiology is now a rapidly expanding field. Marine sponges produce numerous bioactivecompounds with promising pharmaceutical properties. Sponges are well known to harbor diversemicrobes and represent a significant source of bioactive natural compounds derived from the marineenvironment. Recent studies of the microbial communities of marine sponges have uncovered previouslyundescribed species and an array of new chemical compounds. Microbial symbionts in marine spongesoffer potential sources of marine natural products and serve as marine natural product factory thatsupplies bioactive compounds in a sustainable way.